2014
DOI: 10.1080/15205436.2014.891137
|View full text |Cite
|
Sign up to set email alerts
|

Humor Works in Funny Ways: Examining Satirical Tone as a Key Determinant in Political Humor Message Processing

Abstract: This multi-experiment study builds upon extant political entertainment theory, testing whether satire type (horatian versus juvenalian) cues varying processing mechanisms (message discounting versus resource allocation), and if consequential differences to argument scrutiny levels or message persuasiveness result. Using novel stimuli (e.g., animated cartoons, study one) and real-world late-night political satire (The Daily Show and The Colbert Report, study two), results suggest that satire type was a key ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…Similarly, satirical content has been shown to evoke more positive thoughts toward the targeted subject than critical news (LaMarre & Walther, 2013): Rather than scrutinizing the message's target, people scrutinize the satirical message because it provides cues not to be taken seriously. This discounting mechanism was also found in the processing of different types of satire (LaMarre et al, 2014), horatian and juvenalian satire, which differ not only in the conduct of aggression and laughter but also on the degree of judgment implicitness (Holbert, 2014). Lighter forms of humor (horatian satire) were perceived as funnier and less serious than bitter approaches to humor (juvenalian satire; LaMarre et al, 2014).…”
Section: When Is Political Satire Perceived As Funny and When Is It Not?mentioning
confidence: 91%
“…Similarly, satirical content has been shown to evoke more positive thoughts toward the targeted subject than critical news (LaMarre & Walther, 2013): Rather than scrutinizing the message's target, people scrutinize the satirical message because it provides cues not to be taken seriously. This discounting mechanism was also found in the processing of different types of satire (LaMarre et al, 2014), horatian and juvenalian satire, which differ not only in the conduct of aggression and laughter but also on the degree of judgment implicitness (Holbert, 2014). Lighter forms of humor (horatian satire) were perceived as funnier and less serious than bitter approaches to humor (juvenalian satire; LaMarre et al, 2014).…”
Section: When Is Political Satire Perceived As Funny and When Is It Not?mentioning
confidence: 91%
“…This research suggests that political satire shapes a wealth of outcomes, including media habits and choices, attitudes toward politicians, interest in the political process, knowledge about politics, and the desire to participate and engage both civically and politically (Baek and Wojcieszak, ; Baum, ; Baumgartner and Lockerbie, ; Baumgartner and Morris, ; Becker and Bode, ; Cao, ; Feldman and Young, ; Hoffman and Young, ), although effects vary for different populations (Boukes et al., ; Innocenti and Miller, ). On balance, research has also shown that political comedy is seen as both a source of news and entertainment, often offers as much factual and contextual information as traditional network news programming, and can present a space for a more deliberative conversation about politics and public affairs than is currently offered on cable television news networks (Baym, ; Becker, ; Fox, Koloen, and Sahin, ; LaMarre et al., ; Purcell, Heitmeier, and Van Wyhe, ; Young, ). Importantly, political satire has experienced significant growth since 2014, with new offerings across a range of network and cable television outlets (e.g., Full Frontal with Samantha Bee, The Daily Show with Trevor Noah, Last Week Tonight with John Oliver ).…”
mentioning
confidence: 99%
“…How political humor may associate with attitudes toward political candidates (Moy, Xenos, and Hess, ; Young, , ), public affairs (Tsfati, Tukachinsky, and Peri, ), political institutions, and political efficacy (Balmas, ; Rill and Cardie, ) is the subject of others. Finally, how individuals process (Boukes et al., ; Holbert et al., ; LaMarre and Walther, ; Young, ) and perceive (Hoffman, ; LaMarre, ; LaMarre, Landreville, and Beam, ; LaMarre et al., ) politically humorous content is the focus of still others.…”
Section: Political Humor Viewership Effects Scholarshipmentioning
confidence: 99%